Randomised post-test-only study of glutathione and ursodeoxycholic acid combination therapy on liver fibrosis in biliary atresia animal model - Prasetyo, Agung Aji; Surya, Fransisca; Rachmawati, Banundari; Riwanto, Ignatius (Edelweiss Applied Science and Technology, 2025)
Biliary atresia (BA) is a fatal disease and one of the leading causes of liver transplantation in children. The incidence of BA varies worldwide, ranging from 1 in 5,000 to 18,000 newborns. BA is fatal if left untreated, and hepatic portoenterostomy remains the best treatment option. However, the success of this procedure is related to the degree of fibrosis and the timing of the process. This study aimed to observe the use of a glutathione and ursodeoxycholic acid (UDCA) combination as adjuvant therapy that can be administered to delay hepatic fibrosis before hepatic portoenterostomy in Sprague Dawley rats with biliary atresia. Twenty-eight male Sprague Dawley rats were divided into four groups (n = 7 per group); the control group (C) received 20 mg UDCA, trial group 1 (T1) received 10 mg UDCA and 10 mg glutathione, trial group 2 (T2) received 20 mg UDCA and 15 mg glutathione, and trial group 3 (T3) received 30 mg UDCA and 20 mg glutathione. The rats underwent bile duct ligation to induce cholestasis, and the treatment was administered for 21 days. Liver samples were collected to evaluate α-SMA levels. The combination of glutathione and UDCA downregulated α-SMA expression in a dose-dependent manner (p = 0.009). The post-hoc test results showed a lower level of α-SMA expression in group T3 than in groups C (p = 0.002) and T1 (p = 0.005). We conclude that the combination of glutathione and UDCA significantly decreases α-SMA levels in the BA rat model.